2019
DOI: 10.36632/mejar/2019.8.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different NPK fertilization levels and humic acid rates on growth, yield and chemical constituents of roselle (Hibiscus sabdariffa L.)

Abstract: In order to study the influence of NPK fertilization levels (0.0, 50, 75 and 100 of recommended dose), humic acid rates (0.0, 2.0 and 4.0 l/fed.-1 as foliar spray) and their combinations on growth and productivity of roselle, two field experiments were conducted for two summer seasons of 2017 and 2018 at the Experimental Farm of Faculty of Agriculture (Ghazala Farm), Zagazig University, Egypt. The recommended dose (RD) of NPK were (N fertilizer at 68 + P2O5 fertilizer at 32 + K2O fertilizer at 24 kg/fed.-1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The results of the same table showed that the fertilizer combinations caused a significant effect on the plant height, as the C6 combination gave the highest average plant height 195.05 cm, and it did not differ significantly from the average of the C5 combination, which amounted to 189.05 cm, compared to the C0 treatment (no addition), which gave an average 138.45 cm, with an increase of 40%, while combinations C1, C2, C3 and C4 gave averages of 148.45, 153.65, 165.2 and 175.75 cm, respectively. This superiority may be attributed to the role of KPN fertilizer combinations in stimulating cell division and elongation, which provided a suitable environment for plant growth and thus increased the efficiency of the photosynthesis process and increased the representation of dry matter in the plant, which was reflected in the length of one internode and also the number of internode, and thus was reflected positively in the height plant, especially when the soil suffers from A decrease in the level of NPK [10].…”
Section: Plant Height (Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the same table showed that the fertilizer combinations caused a significant effect on the plant height, as the C6 combination gave the highest average plant height 195.05 cm, and it did not differ significantly from the average of the C5 combination, which amounted to 189.05 cm, compared to the C0 treatment (no addition), which gave an average 138.45 cm, with an increase of 40%, while combinations C1, C2, C3 and C4 gave averages of 148.45, 153.65, 165.2 and 175.75 cm, respectively. This superiority may be attributed to the role of KPN fertilizer combinations in stimulating cell division and elongation, which provided a suitable environment for plant growth and thus increased the efficiency of the photosynthesis process and increased the representation of dry matter in the plant, which was reflected in the length of one internode and also the number of internode, and thus was reflected positively in the height plant, especially when the soil suffers from A decrease in the level of NPK [10].…”
Section: Plant Height (Cm)mentioning
confidence: 99%
“…Potassium is essential for many important physiological activities and processes, such as the process of carbon analysis and the transfer of nutrients resulting from the process of carbon metabolism to the lower organs of the plant [9] in addition to activating enzymes and reducing the absorption of harmful ions such as sodium. (Na +2 ) and iron ions in silty and saline soils [10]. Studying the process of balance between these three elements, which are called the main elements, is of great importance, as the presence of an element in the soil solution in a quantity that exceeds the other elements has a negative effect on the absorption of the other elements.…”
Section: Introductionmentioning
confidence: 99%